QSAR-3D e Docking Molecular de Derivados de Ácidos N-arilantranílicos com Atividade Inibitória na Enzima Catepsina L - Camila da Câmara Lopes; Renato Queiroga Pordeus; Arlene Gonçalves Corrêa; Boaz Galdino de Oliveira; Mauro Alves Bueno (Orbital: The Electronic Journal of Chemistry, 2016)
In this work, a molecular modeling study of N-arylanthranilic acid derivatives with inhibitory action on the Cathepsin L enzyme in presented. Firstly, a 3DQSAR study was carried out in order to identify the most important molecular fields, in particular those formed by the C=O, C─O─C and ─NO2 groups, by which the experimental biological activity data were satisfactorily predicted through the correlation (R2 = 0.99) and determination (Q2 = 0.66) coefficient values. In agreement with the noncompetitive inhibition mechanism, the molecular docking calculations revealed that preferential interactions pose outside of the Cathepsin L active site. The correlation between the docking scores and biological activity data are fairly linear, indicating that the strongest and weakest bonded compounds are those with highest and lowest biological activities, respectively.DOI: http://dx.doi.org/10.17807/orbital.v1i1.714